ELECTRONIC ABSORPTION SPECTRA OF FE2+ IONS IN OXYGEN-BASED ROCK-FORMING MINERALS AT TEMPERATURES BETWEEN 297 AND 600 K - Taran M.N.; Langer K. (My University, 2001)
Polarized electronic single crystal spectra of natural Fe2+ ion-bearing oxygen-based minerals, in which ferrous ions enter octahedral sites of different symmetry and distortion (olivine, cordierite, ortho- and clinopyroxene, amphibole), eightfold sites in garnet (almandine) and clinopyroxene (M2), and tetrahedral sites in spinel, were studied at temperatures from 300 to ca. 600 K. In the minerals studied, the spin-allowed bands of Fe2+ display rather variable temperature behaviour. In most cases, due to the thermal expansion of the Fe2+-bearing polyhedra, bands shift to lower energies upon increasing temperature, though there are some exceptions to this rule: in cases of other than sixfold octahedral or close to octahedral coordination, in almandine and spinel the bands shift to higher energies, which can be explained by an increase in distortions of the Fe2+-bearing polyhedra. Splitting of the excited 5E g-level of Fe2+ ions usually, but not always, increases with temperature, reflecting thermally induced increase in distortion of the Fe2+-bearing sites in the minerals studied. Integral intensities of the bands in question do not always obey the general rule, according to which intensity should increase with temperature, when the 3d N-centred site is centrosymmetric, or should remain unchanged when the 3d N site lacks an inversion centre. The experimental results show that the response of the characteristics of absorption bands such as width, intensity and energy caused by dd transitions of Fe2+ in oxygen-based minerals to increasing temperature is not always uniform and is at variance with expectation. This temperature dependence cannot be used directly to solve band assignment problems, as earlier proposed in the literature.